Does high onion plant density increase nitrogen demand? - Vidigal, Sanzio Mollica (2023)
An adequate N supply is essential for plant growth, and changing plant density increases nitrogen demand. The objective of this work was to evaluate the effect of top-dressing nitrogen fertilization on quality and yield of onions grown under three plant densities. The experiment was conducted from June to October, in Oratórios, state of Minas Gerais, Brazil, using the hybrid Superex. A randomized block experimental design was used, with a split-plot arrangement and four replications. N rates (0, 60, 120, and                240 kg ha-1) were evaluated in the plots and plant densities                      (40 plants m-2 - one seedling per cell; 80 plants m-2 - two seedlings per cell; and 120 plants m-2 - three seedlings per cell) were evaluated in the subplots. The yield found for the treatment with 80 plants m-2 and 171 kg ha-1 of N was 51.28 Mg ha-1 of marketable bulbs, with approximately 75% class 3 and 17% class 4 bulbs. Bulb weight decreased with increasing plant density. Top-dressing nitrogen fertilization increases the quality and yield of onions, regardless of the plant density. The highest yield was found when using                80 plants m-2 and 240 kg ha-1 of N. A density of 80 plants m-2 (two seedlings per cell) and 171 kg ha-1 of N is recommended when intending to obtain class 3 and 4 bulbs.